Inhibition of Heme Oxygenase-1 by Zinc Protoporphyrin IX Improves Adverse Pregnancy Outcomes in Malaria During Early Gestation - Cariaco, Yusmaris; Almeida, Marcos Paulo Oliveira; Araujo, Ester Cristina Borges; Briceño, Marisol Patricia Pallete; Durán-Rodriguez, Andrea Tatiana; Franco, Rodrigo Rodrigues; Espindola, Foued Salmen; Silva, Neide Maria (Frontiers in Immunology, 2022)
The enzyme heme oxygenase-1 (HO-1) has cytoprotective effects by catalyzing the degradation of heme to produce carbon monoxide, iron and biliverdin. Furthermore, HO-1 activity has been associated with successful pregnancy. On the other hand, in the context of certain inflammatory conditions, HO-1 can induce iron overload and cell death. To investigate the role of HO-1 in gestational malaria, pregnant BALB/c mice were infected with Plasmodium berghei ANKA in early, mid and late gestation. We found that malaria affected the pregnancy outcome in the three periods evaluated. However, only poor pregnancy outcomes in early pregnancy were related to HO-1 upregulation, iron overload, lipid peroxidation and necrosis of the decidua, which were prevented by HO-1 inhibition. In conclusion, HO-1 expression must be finely tuned in gestational malaria to avoid the deleterious effect of increased enzyme activity.